2022
DOI: 10.1108/sbr-06-2022-0172
|View full text |Cite
|
Sign up to set email alerts
|

Does GRI compliance moderate the impact of sustainability disclosure on firm value?

Abstract: Purpose This paper aims to examine the moderating role of global reporting initiative (GRI) compliance in the association between sustainability reporting and firm value. Design/methodology/approach This study investigates a sample of 223 manufacturing firms, encompassing 11 industries from 2010 to 2019. Using GRI compliance as a moderator, the authors employed a generalized method of moments model to study how sustainability disclosure impacts firm value. Findings The results indicate a positive and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…The regression results demonstrate that ESG disclosure is significantly and positively related to firm value, as measured by Tobin's Q, which supports our first hypothesis which is H1:ESG disclosure has a positive effect on firm value (Tobin's Q). This finding aligns with the views of previous scholars (Aboud & Diab, 2018;Mohammad & Wasiuzzaman, 2021;Sreepriya et al, 2023) who also supported this hypothesis. And there is no relationship between ESG disclosure and firm value (ROE), contrary to our second hypothesis.…”
Section: Regression Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The regression results demonstrate that ESG disclosure is significantly and positively related to firm value, as measured by Tobin's Q, which supports our first hypothesis which is H1:ESG disclosure has a positive effect on firm value (Tobin's Q). This finding aligns with the views of previous scholars (Aboud & Diab, 2018;Mohammad & Wasiuzzaman, 2021;Sreepriya et al, 2023) who also supported this hypothesis. And there is no relationship between ESG disclosure and firm value (ROE), contrary to our second hypothesis.…”
Section: Regression Resultssupporting
confidence: 93%
“…This scepticism arises from the concern that firms may use ESG information disclosure to conceal wrongdoings and highlight positive aspects of their operations. These ESG disclosures might not be independently verified, causing investors to doubt the authenticity of such information (Sreepriya et al, 2023). In a recent study Sun et al (2023), based on the Chinese context, it was found that the level of integration of ESG disclosures is negatively associated with firm value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Barney (1991) Finally, institutional theory states that due to the social contract between society and business, companies must act in a manner consistent with societal requirements. Therefore, businesses engage in ESG reporting in order to comply with the implied social contract and gain legitimacy for their existence (Sreepriya et al, 2023). The institutional theory explores the relationship between firms and society, suggesting that firms are actually influenced by a wide range of external social structures, including public or private rules and organizations such as NGOs that oversee firm activities (Campbell, 2007;Dimaggio & Powell, 1983).…”
Section: Theories Analysismentioning
confidence: 99%
“…The sustainability performance depicted through the ESG Disclosure is becoming increasingly important in the eyes of investors due to increased investor awareness of how their funds are allocated and changes in the rules for reporting sustainability performance which were originally voluntary but now become mandatory for several industrial sectors. Research by Pulino (2022) and Sreepiya (2023), shows that there is a positive effect of ESG disclosure on company value (Pulino et al, 2022;Sreepriya et al, 2023). Meanwhile, Behl (2022) describes a negative effect, while Ihsani (2021) describes the absence of a correlation between the two variables.…”
Section: Source: Indonesia Central Securities Depositorymentioning
confidence: 99%